E-Book The Design of an Interactive Game-Based E-Book to Improve Critical Thinking Skills among Grade XI High School Students in History Learning - Septya Novena Elwana Putri; I Made Tegeh; I Komang Sudarma (Universitas Pendidikan Ganesha, 2025)
History learning that is still dominated by conventional, teacher centered approaches tends to cause student boredom and does not optimally support the development of critical thinking skills, particularly among Generation Z learners. This condition highlights the need for innovative, interactive, and contextual learning media. This study aims to analyze the validity, practicality, and effectiveness of a game based interactive E-Book as a history learning medium in enhancing senior high school students’ critical thinking skills. This research employed a Research and Development (R&D) method using the 4D model, consisting of the define, design, develop, and disseminate stages. The research subjects involved eleventh grade students and history teachers. Data were collected through questionnaires, expert validation, and achievement tests, using validation sheets, response questionnaires, and objective test instruments. Data analysis was conducted using descriptive quantitative analysis, paired sample t-test, and N-Gain analysis. The results indicated that the developed media achieved a very high level of validity and practicality, with student and teacher responses exceeding 98%. In addition, the findings demonstrated a significant improvement in students’ critical thinking skills after using the media, with the N-Gain value falling into the effective category. The study concludes that the game based interactive E-Book is suitable for use as a history learning medium that supports active and meaningful learning. The implications of this study suggest that integrating game-based digital media can serve as a strategic alternative for fostering higher-order thinking skills in history education.